An Assessment of Reuse of Light Ash from Bayer Process Fluidized Bed Boilers in Geopolymer Synthesis at Ambient Temperature - Woshington S. Brito; André L. Mileo Ferraioli Silva; Rozineide A. A. Boca Santa; Kristoff Svensson; José Antônio da Silva Souza; Herbert Pöllmann; Humberto Gracher Riella (Advances in Materials Science and Engineering)
Sustainable civil construction in the future, besides having low energy consumption and greenhouse gas emissions, must also adopt the principle of reusing wastes generated in the production chain that impact the environment. The aluminum production chain includes refining using the Bayer process. One of the main wastes produced by the Bayer process that has an impact on the environment is fly ash. Geopolymers are cementitious materials with a three-dimensional structure formed by the chemical activation of aluminosilicates. According to studies, some are proving to be appropriate sources of Al and Si in the geopolymerization reaction. The research reported here sought to assess the possibility of reusing fly ash characteristic of the operational temperature and pressure conditions of Bayer process boilers in geopolymer synthesis. Geopolymerization reaction was conducted at an ambient temperature of 30°C, and the activator used was sodium hydroxide (NaOH) 15 molar and sodium silicate (Na2SiO3) alkaline 10 molar. Fly ash and metakaolin were used as sources of Al and Si. XRD, XRF, and SEM Techniques were used for characterizing the raw materials and geopolymers. As a study parameter, the mole ratios utilized followed data from the literature described by Davidovits (year), so that the best results of the geopolymer samples were obtained in the 2.5 to 3.23 range. Resistance to mechanical compression reached 25 MPa in 24 hours of curing and 44 MPa after 28 days of curing at ambient temperature.